A dynamic analysis of a SAGSHP system coupled to solar thermal collectors and photovoltaic-thermal panels under different climate conditions. (1st June 2020) - Emmi, Giuseppe; Bordignon, Sara; Zarrella, Angelo; De Carli, Michele
Highlights: Use of solar energy source in ground source heat pump applications. Comparison of solar thermal collectors and photovoltaic hybrid panels. Effects of climate on thermal and energy behaviour of the SAGSHP system. The use of PVT panels increases the global COP of the system. The multi-source energy system increases RES exploitation. Abstract: The use of multi-source energy systems is a promising technical solution for the reduction of greenhouse gases emissions and, at the meantime, for enhancing the exploitation of renewable energy sources. The present paper analyses a Solar Assisted Ground Source Heat Pump system and tries to fill the gap in the literature, where a direct comparison between the consolidated solar thermal technology and the emerging and widely discussed photovoltaic thermal technology is missing. Indeed, the two different devices for the exploitation of solar energy have been analysed through dynamic simulations carried out in TRNSYS environment. Through this approach, it is possible to investigate and predict in detail the thermal and electrical behaviour of the energy system, composed by a water-to-water heat pump, which withdraws from two thermal reservoirs that are connected to a solar loop, composed either of solar thermal collectors or of photovoltaic thermal panels and to a ground loop. The heat pump is used to provide space cooling and space heating to a residential building, through fan coil terminal units or radiant floor system. Furthermore, the heat pump system assists the solar field in the production of domestic hot water. This study looks at the development of a flexible system able to work in different operating conditions. The model's boundary conditions can be changed for simulating a variety of case studies as the weather condition, the building load and the domestic hot water profile can be easily changed, together with specific components' parameters. The control strategy makes it possible to vary the setpoint temperatures for simulating different operating conditions and management choices. In this way, the user can easily adapt the model functions to a specific plant system. The operating conditions of the two systems layouts have been compared and the energy performances evaluated for three case studies characterised by the weather conditions of the European cities of Berlin (mild-cold climate), Venice (mild climate) and Barcelona (mild-warm climate), and the corresponding thermal load profile of a two-storey building with a useful floor area of 170 m 2 . The study shows the possibility to directly exploit the solar energy for the domestic hot water production and as a heat source for the heat pump. The results from the comparison between the two systems' configurations, with photovoltaic thermal panels and with solar thermal collectors, prove that there is the possibility to obtain a relevant improvement in the efficiency of the heat pump using photovoltaic thermal panels. The investigated multi-source energy system, moreover, allows an optimal employment of the available renewable heat sources and could easily be applied to case studies characterized by different boundary conditions.